2013
DOI: 10.1016/j.crohns.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intensive granulocyte and monocyte adsorptive apheresis in patients with ulcerative colitis positive for cytomegalovirus

Abstract: Background and aim: Cytomegalovirus (CMV) exacerbates ulcerative colitis (UC) refractory to immunosuppressive therapies. The conditions under which CMV reactivation occurs in patients with UC, however, is unclear. In addition, the diagnostic and treatment strategies for UC positive for CMV have not been established. Granulocyte and monocyte adsorptive apheresis (GMAA) is natural biological therapy for UC in which the granulocytes/macrophages producing inflammatory cytokines are removed. We investigated the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Intensive GMAA treatment (twice per week, 10 sessions) was performed as previously described [11,12,16] for all patients with CD. Blood was accessed via the antecubital vein in one arm, and from the outflow blood was returned to patients via the antecubital vein in the other arm through 19 gauge needles.…”
Section: Methodsmentioning
confidence: 99%
“…Intensive GMAA treatment (twice per week, 10 sessions) was performed as previously described [11,12,16] for all patients with CD. Blood was accessed via the antecubital vein in one arm, and from the outflow blood was returned to patients via the antecubital vein in the other arm through 19 gauge needles.…”
Section: Methodsmentioning
confidence: 99%
“…Yoshino et al [52] demonstrated that 56.7% of UC patients refractory to immunosuppressive therapies were positive for CMV-DNA in colonic mucosa. Fukuchi et al [53] reported that 29.4% of active UC patients without receiving any immunosuppressive therapies were positive for CMV-DNA in their colonic mucosa. In addition, analysis in a newly established mouse model, which resembles human UC with concomitant CMV infection, strongly suggests that CMV infection can trigger intestinal inflammation [54].…”
Section: Prevalence Of CMV Infection In Ibd Particularly Ulcerative mentioning
confidence: 99%
“…This anti-inflammatory mechanism of GMAA comprises a promising treatment for UC patients with concomitant CMV infection because production of proinflammatory cytokines, particularly TNF-α, is strongly associated with colonic CMV reactivation. In fact, 2 Japanese studies reported that GMAA does not induce colonic CMV reactivation and leads to disappearance of colonic CMV replication in previously PCR CMV-DNA-positive UC patients [53, 75]. Thus, GMAA therapy offers optimal inflammatory control without the need for steroids.…”
Section: Treatment Of CMV Infectionmentioning
confidence: 99%
“…It is estimated that CMV infection in IBD patients is within the range of 33–36% in patients with steroid-refractory UC and 21–34% in patients suffering from severe UC (11). Colonic CMV reactivation is considered to be an exacerbating factor in patients with UC and those refractory to immunosuppressive therapies due to the poor prognosis of UC patients with concomitant CMV infection (12). Previous studies have demonstrated that local intestinal inflammation and additional immunosuppressive therapies, such as corticosteroid administration, may induce colonic CMV reactivation in IBD patients (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Colonic CMV reactivation is considered to be an exacerbating factor in patients with UC and those refractory to immunosuppressive therapies due to the poor prognosis of UC patients with concomitant CMV infection (12). Previous studies have demonstrated that local intestinal inflammation and additional immunosuppressive therapies, such as corticosteroid administration, may induce colonic CMV reactivation in IBD patients (12,13). However, another study presented conflicting results on the association of CMV reactivation with the occurrence or severity of IBD exacerbation (1).…”
Section: Introductionmentioning
confidence: 99%